CSC238: Object Oriented Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course is the continuation of the Fundamental of Computer Problem Solving course. It will emphasis on solving simple to more complex problems using a programming language that supports Object-Oriented programming. The main concepts of Object-Oriented programming are discussed. Principles and techniques taught will include objects and classes, abstraction, encapsulation, inheritance and polymorphism. Students will also be taught on how to apply Object-Oriented concepts to store and retrieve data using text files.